High pretreatment neutrophil‐to‐lymphocyte ratio as a predictor of poor survival prognosis in head and neck squamous cell carcinoma: Systematic review and meta‐analysis - Yang, Lin (Head Neck, 2018)
BACKGROUND: The prognostic roles of neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) have been reported in head and neck squamous cell carcinoma (HNSCC), but their results remain controversial. METHODS: A total of 25 literatures with 28 cohorts involving 6847 HNSCC patients were included. The hazard ratio (HR) was pooled with 95% confidence interval (CI) using fixed‐effects or random‐effects models. RESULTS: High pretreatment NLR predicted poor overall survival (OS: HR = 1.68; 95% CI = 1.39‐2.03; P < .001), disease‐free survival (DFS: HR = 1.76; 95% CI = 1.42‐2.17; P < .001), progression‐free survival (PFS: HR = 1.53; 95% CI = 1.09‐2.14; P = .014), and cancer‐specific survival (CSS: HR = 1.45; 95% CI = 1.23‐1.71; P < .001) in HNSCC. However, the association between PLR and OS or DFS was not statistically significant. CONCLUSION: The NLR can serve as a potential prognostic biomarker for patients with HNSCC.